EFFECTS OF ECTOPIC INNER FOVEAL LAYERS ON FOVEAL CONFIGURATION AND VISUAL FUNCTION AFTER IDIOPATHIC EPIRETINAL MEMBRANE SURGERY. Issue 8 (August 2022) - Yang, Xiaohan; Wang, Zengyi; Yu, Yanping; Mo, Bin; Zhang, Ke; Wu, XiJin; Liu, Lingzi; Wang, Xinbo; Qi, Biying; Liu, Wu
Abstract : The ectopic inner foveal layer is a negative factor for postoperative anatomical recovery and preoperative visual acuity, but its impact on postoperative visual acuity is small. Foveal configuration at 1 month after surgery is associated with the long-term outcome. Abstract : Purpose: To investigate the effects of ectopic inner foveal layers (EIFLs) on foveal configuration recovery and visual acuity after idiopathic epiretinal membrane removal and analyze the relationship of foveal configuration recovery between 1-month and long-term postoperatively. Methods: This retrospective study included 216 consecutive eyes with idiopathic epiretinal membrane that underwent vitrectomy surgery. A comprehensive ophthalmic examination was performed for all patients before and 1, 4, 10, and 24 months after surgery. We observed the postoperative anatomical and functional recovery of eyes with and without EIFLs and analyzed the association between short-term and long-term anatomical recovery. Results: The presence of EIFL was associated with severe preoperative visual damage ( P < 0.001) and was considered as a negative factor for postoperative foveal depression recovery ( P < 0.001). No significant difference was found in postoperative best-corrected visual acuity between the eyes with and without EIFLs ( P = 0.442). For eyes with Stage II epiretinal membranes, 17.6% developed EIFLs postoperatively, which did not affect the final best-corrected visual acuity. Overall, 24.5% of epiretinal membranes restored the foveal configurations at 1 month postoperatively, and 14.7% continued recovering during the follow-up. Foveal structure recovery in eyes with EIFLs was associated with earlier stage, fewer microcystic macular edema, complete interdigitation zone layer, and a thinner central foveal thickness (all P < 0.05) at 1 month postoperatively. Conclusion: The EIFL is associated with severe preoperative visual damage and is a negative factor for postoperative anatomical recovery, but it is a minor factor for postoperative visual acuity. We also found an association of foveal configuration recovery between 1 month and long-term after surgery.